POTENSI KONFLIK PENGGUNAAN LAHAN PERSAWAHAN DI KABUPATEN GOWA PADA KAWASAN STRATEGIS NASIONAL MAMMINASATA: Potential Conflicts of The Rice Field Land-Use in Gowa District on Mamminasata National Strategic Area - Zulkarnain Chairuddin; Pratama Putra; Sumbangan Baja (Jurnal Ecosolum, 2021)
The rate of the population growth was accompanied with the increased number of economic growth year by year in Gowa District on the KSN Mamminasata trigger the competition of using the potential land leading to the land-use conflicts. This research aims to assess the rice field land-use potential conflicts. The map of land-use, the map of spatial pattern of RTRW in Gowa District, and the agricultural land for sustainable food crops zonation map was interpreted and collated to get a general overview of potential land-use conflicts that may occur and determine potential conflicts of government regulation sector. Then interviews were conducted with farmers using a purposive sampling questionnaire method to determine their land use preferences for the land they currently manage. It is then tabulated in the form of a typology to describe the distribution of potential land use conflicts. The results showed that the existing irrigated rice fields in Gowa District spread over nine sub-districts which all are included in the KSN Mamminasata with the total area at 19,053.27 ha and the rest of 4,229.65 ha were not included in the plan of the wetland agricultural areas, yet those belong to in residential and educational areas. In addition, there was land at 2,493.26 ha included in the zonation ALSF and ARLSF. There were 17 villages which had the higher number of rice field preferences than the residential preferences. The differences from these land-use preferences can trigger into the land-use conflicts between the parties occurred.